please help with answer solve question 3
Attachments:
![](https://hi-static.z-dn.net/files/d46/9674e5ca6fa5767cad15797e39f84f5b.jpg)
Answers
Answered by
1
we have, angle AOB = angle COD
subtracting angle COB from both
AOB - COB = COD - COB
AOC = BOD
Now in triangle AOC and BOD ,
AO = OB (given)
OC = OD (given)
angle AOC = angle BOD ( proved)
hence , triangle AOC is congruent to triangle
BOD
so AC = BD (C.P. C.T)
Hope it helps you
Mark me as Brainliest please
subtracting angle COB from both
AOB - COB = COD - COB
AOC = BOD
Now in triangle AOC and BOD ,
AO = OB (given)
OC = OD (given)
angle AOC = angle BOD ( proved)
hence , triangle AOC is congruent to triangle
BOD
so AC = BD (C.P. C.T)
Hope it helps you
Mark me as Brainliest please
Similar questions